Penta Graph Topological Space: A New Perspective in Graph Induced Topology - R.Mohanapriya; B.Sasireka; S.Santhiya (Utilitas Mathematica, 2025)
The primary objective of this paper is to introduce the concepts of lower penta subgraph, upper penta subgraph, and boundary penta subgraph. Based on these foundational structures, the author defines a new topological framework called the Penta graph topological space. Furthermore, several fundamental properties of this new topological space are discussed and established.